2019
DOI: 10.1002/jat.3931
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure of arsenic and fluoride and their combined toxicity: A recent update

Abstract: Environmental exposure to arsenic (As) and fluoride (F) in the recent year has been increased because of excessive use of naturally contaminated ground water.Surface water is also regularly contaminated with these elements in various industrial areas. Arsenicosis and fluorosis upon individual exposure of As and F are reported in many studies. A syndrome of endemic As poisoning and fluorosis occurs during concurrent exposure of As and F. Previous reports showed synergistic, antagonistic and independent effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Note that the reduced form of glutathione is a key endogenous antioxidant that participates in scavenging of ROS [ 2 ]. Production of ROS due to the interconversions between pentavalent and trivalent forms during methylation process and conjugation of arsenic with glutathione for renal excretion is known to deplete GSH [ 54 ]. This study sought to determine the ability of CoQ 10 and DMSA to protect from arsenite-driven GSH depletion and induction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the reduced form of glutathione is a key endogenous antioxidant that participates in scavenging of ROS [ 2 ]. Production of ROS due to the interconversions between pentavalent and trivalent forms during methylation process and conjugation of arsenic with glutathione for renal excretion is known to deplete GSH [ 54 ]. This study sought to determine the ability of CoQ 10 and DMSA to protect from arsenite-driven GSH depletion and induction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic arsenicosis, referred to as ground arsenicosis, is a biogeochemical disease that seriously endangers human health and can be divided into drinking water-type arsenicosis and coal-burning-type arsenicosis (Mondal and Chattopadhyay, 2020). Arsenic accumulates in the body, causing not only skin lesions and peripheral nervous system damage but also damage to some organs and tissues (Wang et al, 2019; Yao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the World Health Organization (WHO) listed them as the most important inorganic pollutants in water (Lopez-Guzman et al 2019). In addition, studies have shown that arsenic and fluoride have combined toxicity to the human body (Mondal and Chattopadhyay 2020), and the combined effect of arsenic and fluoride also affects children's intelligence, growth and development (Wang et al 2006). However, arsenic and fluoride in water are usually accompanied (Kim et al 2012), especially in arid or semi-arid areas, the co-occurrence of fluoride and arsenic is common, such as Latin America (Alarcon-Herrera et al 2013) and Pakistan (Farooqi et al 2007).…”
Section: Introductionmentioning
confidence: 99%